PEMBUATAN NUGET JAMUR TIRAM PUTIH DENGAN PENAMBAHAN IKAN GABUS - Mercia Yolanda Ashari; Usman Pato; Evy Rossi (Fakultas Pertanian Universitas Riau, 2022)
The purpose of this research was to obtain the best combination for making white oyster mushroom nuggets with the addition of cork fish. This study was conducted by using a completely randomized design with four treatments and four replications. The treatments consisted of TG1=white oyster mushroom : cork fish (100:0), TG2=white oyster mushroom : cork fish (90:10), TG3 = white oyster mushroom : cork fish (80:20), TG4 = white oyster mushroom : cork fish (70:30). Data obtained were analyzed by using analysis of variance and followed by Duncan’s New Multiple Range Test (DNMRT) at 5%.Result showed that the combination of white oyster mushroom and cork fish significantly affected moisture, ash, fat, protein, and fiber, and descriptive sensory assessment such as colour, flavour, aroma and elasticity of nuggets. The best treatment was TG4 = white oyster mushroom : cork fish (70:30) with 54.91% moisture content, 1.71% ash, 12.62% fat, 35.24% protein, and 0.28% fiber. The overall sensory assessment of TG4 treatment was favored by panelists with a description of yellowish white colour, a taste typical of cork fish, a little bit of typical smell of cork fish and white oyster mushroomand chewy texture.